Вы находитесь на странице: 1из 6

..

.

= 0 e ( )


= 0 e ( )

)
= 0 e (

) ) )
0 e ( + 0 e ( = = 0 e (
( ) ( ) ( )
0 e + 0 e =
= 0 e

Ae + Be = Ce


Ae + Be = Ce (1)
1
( Ae + Be )= Ce (2)

12

( )e = e

= =
= sin sin sin sin
= =
= sin 1 1 2

= sin
= 1

=

sin 1 2 2

= = = =
sin 2 1 1
1


=
1

=
2
.


xz, -0 To = 0)
2
= = 2 =
4 4

1 2 sin2
=
4 sin2 +
2 2 4 sin2 cos 2
=
4 sin2 +

1 2 2
=
4 tg 2 +
2 2 4 sin2 cos 2
=
4 sin2 + co 2
1 1 2
= 2 + 2 =
4 2

sin 2 cos 2 [1 cos 2 ( )] n2


I 2I
sin ( ) cos ( )
2 2
n1
sin 2
( ) tg 2
( )
I 12 I 2 2
sin ( ) tg ( )

0 2 0 2 2
+ 21 1
= = 2 = 2
1 + 2 21 + 1